2012
DOI: 10.4278/ajhp.110516-qual-199
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Physiological Response of Students to Different Types of Stress Management Programs

Abstract: The combination of deep breathing, relaxation response, meditation, and guided imagery techniques with CB seems to be effective at helping people to deal with stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…The relaxation response can be effective in offsetting the negative psychobiological effects of stress through mind-body approaches such as meditation, guided imagery, and controlled breathing [33,34]. Research has shown that relaxation training elicits changes in peripheral blood gene expression [35], while others have shown significant differences in gene expression between Qigong practitioners and normal controls [36].…”
Section: Discussionmentioning
confidence: 99%
“…The relaxation response can be effective in offsetting the negative psychobiological effects of stress through mind-body approaches such as meditation, guided imagery, and controlled breathing [33,34]. Research has shown that relaxation training elicits changes in peripheral blood gene expression [35], while others have shown significant differences in gene expression between Qigong practitioners and normal controls [36].…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of techniques having positive impacts on mood and energy (both physical and mental), pranayama produced a significantly greater positive impact on mood and energy than relaxation and visualization techniques (Wood 1993). A study examining stress management, found that deep breathing, relaxation, meditation, and guided imagery techniques resulted in reduced levels of anxiety, anger, neuroticism, hopelessness, salivary cortisol, and respiration levels (Iglesias et al 2012). Deep breathing exercises have also been shown to reduce PTSD-like symptoms and normalized abnormal cortisol levels (Kim et al 2013).…”
Section: Breathing and Meditation Techniques For Reducing Negative Emmentioning
confidence: 99%
“…Question 2 was selected for evaluating the frequency of relaxation. Relaxation has a stress-buffering effect and is useful to reduce the accumulation of stress (Iglesias et al 2012;Jerath et al 2015;Linnemann et al 2017). Question 3 was employed for evaluating the frequency of eating when irritated or worried, which contributes to emotional eating.…”
Section: Epworth Sleepiness Scale (Ess) and Measurements Of Scores Fomentioning
confidence: 99%